Testing of SMRT train door system 1 - Khoo, Lih Yan (2017)
The Mass Rapid Transit (MRT) is the main constituent of the railway structure in Singapore, coming second to Manila’s LRT System, which is the oldest subway system in Southeast Asia. Since its operation in 1987, the MRT has been improving alongside Singapore’s progress as a state. Due to the long-running operation of the MRT, train faults which inevitably occurs, hindering passengers’ time on-board. This poses a problem, where the train had to be brought back to the depot for maintenance. A test concluded that the train doors were unable to close intermittently. Thus, this project aims to develop a method for the detection of train door faults, that will help with monitoring train doors. With the aid of this development, the time taken for maintenance of train doors will be reduced, which can lighten the workload of maintenance teams. Since the current system only monitors the status at which train doors are opened and closed, exact faulty components are unlikely to be pinpointed.